Social legal security for victims of domestic violence in Kazakhstan - Surkova С.С.; Saktaganova И.С. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2023)
The purpose of this article is to identify the imperfection of the legislation on social protection of victims of domestic violence and to propose some amendments to the legislation of Kazakhstan. The authors use the method of comparative analysis of the current legislation of Kazakhstan and other countries in the field of social protection of people subjected to domestic violence and in need of social assistance. Currently, Kazakhstan has adopted the Social Code of the Republic of Kazakhstan, which comes into force on 07/01/2023, and according to the authors, it requires significant improvement proposed in the article. One of them is the inclusion in the code of victims of domestic violence as a category of subjects of social protection. The originality is due to the role of the state’s social policy for needy citizens, which should be focused on creating a more ideal system of social protection for certain categories of citizens, including victims of domestic violence. And also, the improvement of legislation in this area. This is not only a constitutional guarantee, but also the sustainable development and stability of society.